Transient Temperature Distribution of Underground Carbon Dioxide Salt Cavern Storage With State Space Model - Yuan, Zhou; Zhou, Yanxi; Wei, Minghui; Liao, Xinwei (Frontiers in Energy Research, 2020)
Underground salt caverns have become one of the potential methods for carbon dioxide (CO2) storage due to its advantages including high storage capacity and easy construction. The wellbore and salt cavern heat transfer models for the CO2 injection process was developed and solved by the state space method. This method can not only solve the partial differential equation, but can also be used as the basic model of automatic control. The results indicate that the temperature of annulus and the salt cavern are significantly influenced by the injection rate during the injection process, while the brine temperature in tubing remains almost unchanged. When the injection process stops, the temperature of annulus and the salt cavern are dominated by the formation temperature. The temperature of tubing brine mainly changes after a few hours, causing crystals to separate out from the brine, which can also explain why the tubing is blocked when the gas injection stops.